2010
DOI: 10.1124/jpet.110.166850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxymetabolites of Bupropion on Nicotine Dependence Behavior in Mice

Abstract: Bupropion is an atypical antidepressant that also has utility as a smoking cessation aid. Hydroxybupropions are major metabolites of bupropion and are believed to contribute to antidepressant and perhaps smoking cessation activities. Because bupropion metabolism is more similar in humans and mice than in humans and rats, the present study investigated effects of hydroxybupropion enantiomers in mouse behavioral models measuring various aspects of nicotine dependence. Bupropion and (2S,3S)-hydroxybupropion, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…Bupropion is used clinically to promote smoking cessation. Animal and human data suggest that bupropion's ability to promote smoking cessation is at least partially mediated by its major plasma metabolite OH-BUP (Damaj et al, 2010;Zhu et al, 2012). At steady state, plasma OH-BUP levels are 10-20 times higher than plasma bupropion levels, and OH-BUP has higher affinity for the a4b2 nicotinic acetylcholine receptors than bupropion (Damaj et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bupropion is used clinically to promote smoking cessation. Animal and human data suggest that bupropion's ability to promote smoking cessation is at least partially mediated by its major plasma metabolite OH-BUP (Damaj et al, 2010;Zhu et al, 2012). At steady state, plasma OH-BUP levels are 10-20 times higher than plasma bupropion levels, and OH-BUP has higher affinity for the a4b2 nicotinic acetylcholine receptors than bupropion (Damaj et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among these metabolites, OH-BUP had the highest steady-state plasma levels, and has been shown to be pharmacologically active ( Fig. 1) (Damaj et al, 2004(Damaj et al, , 2010Zhu et al, 2012;Benowitz et al, 2013). Higher levels of OH-BUP, but not bupropion, were associated with greater rates of smoking cessation in smokers receiving bupropion treatment (Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Different metabolites of bupropion have significant impact on its efficacy, since these metabolites have 25-50% potency compared with bupropion on the basis of antidepressant screening tests in an animal model (Bondarev et al, 2003;Damaj et al, 2004). In addition, the plasma levels of hydroxybupropion are 5-to 10-fold higher than the parent drug bupropion after oral administration of bupropion HCl (Bondarev et al, 2003;Damaj et al, 2004;Jefferson et al, 2005;Damaj et al, 2010;Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…BUP is 4-hydroxylated by CYP2B6 to OHBUP (Faucette et al, 2000;Hesse et al, 2000;Benowitz et al, 2013), whereas the reduction of BUP by 11b-hydroxysteroid dehydrogenase 1 and other carbonyl reductases (Meyer et al, 2013;Connarn et al, 2015) forms two amino alcohol stereoisomers, THRHBUP and ERYHBUP. OHBUP, THRHBUP, and ERYHBUP exhibit pharmacological activity in preclinical models (Martin et al, 1990;Bondarev et al, 2003;Damaj et al, 2004Damaj et al, , 2010 and may mediate BUP-induced seizures (Silverstone et al, 2008). In humans, these metabolites are believed to be responsible for BUP treatment outcomes (Daviss et al, 2006;Dwoskin et al, 2006;Lee et al, 2007;Zhu et al, 2012;Laib et al, 2014) and for clinically observed DDIs between BUP and CYP2D6 substrates (Reese et al, 2008;Parkinson et al, 2010;Yeung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%